GHOSTS POPULARIZED: A TRANSNATIONAL STUDY OF INDONESIAN AND AMERICAN HORROR FILMS - Rudy Rudy; Galant Nanta Adhitya; Ida Rochani Adi (IdeBahasa, 2026)
As a type of horror film widely watched by people in both Indonesia and the United States, ghost-themed movies contain a wealth of information that can be gleaned through research. Indonesian culture, which has various ghost myths, makes the discussion on ghosts interesting and useful, particularly if it is also linked to the transnational perspective. This descriptive research focuses on analyzing ghost characters in Indonesian and American horror films to identify portraits associated with ghosts in Indonesian horror films and to examine the changes occurring in American ghost movies from a transnational perspective. The study incorporated Roland Barthes’ semiotic approach to interpret ghost characters in Indonesian horror movies selected by using the purposive sampling technique to gather the data based on the specific themes needed in the study. The result showed that ghost portraits in Indonesian horror films could signify anger, vengefulness, as well as solitude. Apart from that, by using a transnational perspective to study the phenomena of ghost films in Indonesia and the US, this study found that American ghost movies have developed an American version of ghost characters, and there was a similar pattern – the idea of possession and haunted houses in Indonesian and American ghost films.